High Field Brain MRI : Use in Clinical Practice - Scarabino, Tommaso; Pollice, Saverio; Popolizio, Teresa (Springer International Publishing : Imprint: Springer, 2017)
This richly illustrated book summarizes the state of the art in brain MRI with the 3-Tesla high-field scanner. The aim is to clarify the numerous advantages of using a 3-T high magnetic field MR scanner, especially in terms of sensitivity and specificity. The first section describes techniques for standard MR examination of the brain. Full descriptions are then provided of advanced protocols such as MR angiography, diffusion-weighted imaging (DWI), perfusion-weighted imaging (PWI), MR spectroscopy, MR tractography, and functional imaging. Differences in diagnostic features when performing these examinations at 3 T and at 1.5 T are highlighted. In addition, safety issues relating to the installation and use of a high-field scanner are discussed. The second section then describes and illustrates in detail each of the main clinical applications of 3-T MRI in the human brain: trauma, stroke, white matter disease, Parkinson's disease, Alzheimer's disease, brain tumors, inflammatory disease, psychiatric disorders, etc. A final chapter is dedicated to the evaluation of 7-T MRI within both research and potential clinical settings. The book will be a valuable tool for general radiologists, neuroradiologists, trainees, and technicians.
Keywords: Medicine.; Neuroradiology.; Neurology.; elektronické knihy; electronic books